Photosynthetic regulation in fluctuating light under combined stresses of high temperature and dehydration in three contrasting mosses. (October 2022) - Xia, Hongxia; Chen, Ke; Liu, Lilan; Plenkovic-Moraj, Anđelka; Sun, Geng; Lei, Yanbao
Abstract: Photosynthesis regulation is fundamental for the response to environmental dynamics, especially for bryophytes during their adaptation to terrestrial life. Alternative electron flow mediated by flavodiiron proteins (FLV) and cyclic electron flow (CEF) around photosystem I (PSI) play seminal roles in the response to abiotic stresses in mosses; nevertheless, their correlation and relative contribution to photoprotection of mosses exposed to combined stresses remain unclear. In the present study, the photosynthetic performance and recovery capacity of three moss species from different growth habitats were examined during heat and dehydration with fluctuating light. Our results showed that dehydration at 22 °C for 24 h caused little photodamage, and most of the parameters recovered to their original values after rehydration. In contrast, dehydration at 38 °C caused drastic injuries, especially to PSII, which was mainly caused by the inactivation of non-photochemical quenching (NPQ). Dehydration also induced a high accumulation of O2 - and H2 O2 . A consistently higher CEF as well as a positive correlation between CEF and FLV was observed in resistant R. japonicum, implying CEF played a more important protective role for R. japonicum . In H. plumaeforme and P. cuspidatum, the positive relationship under mild stress switched to negative when stress became severe. Therefore, FLV pathway was sensitive to environmental fluctuations and maybe less efficient than CEF thus, readily to be lost during land colonization and evolution in angiosperms. Our work provides insights into the coordination of various pathways to fine-tune photosynthetic protection and can be used as a basis for species screening and development of breeding strategies for degraded ecosystem restoration with pioneering mosses. Highlights: Moss photosynthetic regulations were investigated under light, temperature and dehydration. Dehydration at 38 °C caused drastic injuries to PSII by NPQ inactivation. A consistently positive relationship between CEF and FLV in resistant R. japonicum . The relationship of CEF and FLV switched to negative under severe stress in susceptible mosses. . FLV was sensitive to environmental fluctuations and readily to be lost during land colonization.